Une statue assise gallo-romaine de tradition celtique à Meillant (Cher) - Sophie Krausz; Gérard Coulon (Revue Archéologique du Centre de la France)
An anthropomorphic stone statue was discovered in the park of the Château of Meillant (Cher) during the 1970s. This article provides a study of this sculpture which will be added to those of a series of Bituriges Gallo-Roman statues in sitting position.